Microbiota dynamics, metabolic and immune interactions in the cervicovaginal environment and their role in spontaneous preterm birth - Onyango, Stanley; Mi, Jia Dai; Koech, Angela; Okiro, Patricia; Temmerman, Marleen; von Dadelszen, Peter; Tribe, Rachel M.; Omuse, Geoffrey; , the PRECISE Network (Frontiers in Immunology, 2023)
Differences in the cervicovaginal microbiota are associated with spontaneous preterm birth (sPTB), a significant cause of infant morbidity and mortality. Although establishing a direct causal link between cervicovaginal microbiota and sPTB remains challenging, recent advancements in sequencing technologies have facilitated the identification of microbial markers potentially linked to sPTB. Despite variations in findings, a recurring observation suggests that sPTB is associated with a more diverse and less stable vaginal microbiota across pregnancy trimesters. It is hypothesized that sPTB risk is likely to be modified via an intricate host-microbe interactions rather than due to the presence of a single microbial taxon or broad community state. Nonetheless, lactobacilli dominance is generally associated with term outcomes and contributes to a healthy vaginal environment through the production of lactic acid/maintenance of a low pH that excludes other pathogenic microorganisms. Additionally, the innate immunity of the host and metabolic interactions between cervicovaginal microbiota, such as the production of bacteriocins and the use of proteolytic enzymes, exerts a profound influence on microbial populations, activities, and host immune responses. These interplays collectively impact pregnancy outcomes. This review aims to summarize the complexity of cervicovaginal environment and microbiota dynamics, and associations with bacterial vaginosis and sPTB. There is also consideration on how probiotics may mitigate the risk of sPTB and bacterial vaginosis.